Bi-continuous pattern formation in thin films via solid-state interfacial dealloying studied by multimodal characterization. Issue 10 (28th June 2019) - Zhao, Chonghang; Kisslinger, Kim; Huang, Xiaojing; Lu, Ming; Camino, Fernando; Lin, Cheng-Hung; Yan, Hanfei; Nazaretski, Evgeny; Chu, Yong; Ravel, Bruce; Liu, Mingzhao; Chen-Wiegart, Yu-chen Karen
Abstract : Solid-state interfacial dealloying creates bi-continuous nanostructured thin films with 3D interconnected morphology, revealed by multimodal characterization, offering potential applications in catalysis, biomedical sensing and energy storage. Abstract : Bicontinuous-nanostructured materials with a three-dimensionally (3D) interconnected morphology offer unique properties and potential applications in catalysis, biomedical sensing and energy storage. The new approach of solid-state interfacial dealloying (SSID) opens a route for fabricating bi-continuous metal–metal composites and porous metals at nano-/meso-scales via a self-organizing process driven by minimizing the system's free energy. Integrating SSID and thin film processing fully can open up a wide range of technological opportunities in designing novel functional materials; to-date, no experimental evidence has shown that 3D bi-continuous films can be formed with SSID, owing to the complexity of the kinetic mechanisms in thin film geometry and at nano-scales, despite the simple processing strategy in SSID. Here, we demonstrate that a fully-interconnected 3D bi-continuous structure can be achieved by this new approach, thin-film-SSID, using Fe–Ni film dealloyed by Mg film. The formation of a Fe–Mg x Ni bi-continuous 3D nano-structure was visualized and characterized via a multi-scale, multi-modal approach, combining electron transmission microscopy with synchrotron X-ray fluorescence nano-tomography and absorption spectroscopy. Phenomena involved with structural formation are discussed. These include surface dewetting, nano-size void formation among metallic ligaments, and interaction with a substrate. This work sheds light on the mechanisms of the SSID process, and sets a path for manufacturing of thin-film materials for future nano-structured metallic materials.